(untitled) (Fiep Bulletin - online, 2013)
The purpose of the study is referred to observe the efficiency of physical education class, using the variable “Time student movement” (TSM), a parameter that gives a reference to the results obtained in the state and national competitions of the physical education class in the basic education in Mexico (students aged between 5 to 14 years old), making a comparative study of TSM, including physical education programs; 1. Dynamic Motor Integration implemented in 1993-2008 and 2. Teaching competency from 2008. In the latter shows the few minutes of practice of students in the objectives. Adding another study concerning to the physical activation at the school “Rhythmic aerobic routines with music”